The Efficacy of Programmed Intermittent Epidural Bolus for Postoperative Analgesia after Open Gynecological Surgery: A Randomized Double-Blinded Study. (15th May 2018) - Satomi, Shiho; Kakuta, Nami; Murakami, Chiaki; Sakai, Yoko; Tanaka, Katsuya; Tsutsumi, Yasuo M.
Abstract : Background . It is well known that the programmed intermittent epidural bolus (PIEB) technique effectively provides epidural anesthesia in labor. This randomized double-blind trial compared the postoperative analgesic efficacy of PIEB with that of continuous epidural infusion (CEI) in patients undergoing gynecological surgery under combined general-epidural anesthesia. Methods . Patients undergoing open gynecological surgery under combined general-epidural anesthesia were randomized at a 1 : 1 ratio to receive PIEB or CEI. In the PIEB group, the pump delivered 4 mL ropivacaine 0.2% plus fentanyl 2 μ g/mL every hour. In the CEI group, the pump delivered the same solution at a rate of 4 mL/h. In both groups, additional 4 mL boluses of ropivacaine 0.2% plus fentanyl 2 μ g/mL were provided, when necessary, by patient-controlled epidural analgesia after surgery. The primary outcome was the total ropivacaine dose 40 hours after surgery. The secondary outcomes were the number of PCEA boluses and postoperative pain (evaluated on an 11-point numerical rating scale) 3, 24, and 48 hours after surgery. Results . In total, 57 patients were randomized (n = 28 and 29 in the PIEB and CEI groups, resp.). The two groups differ significantly in terms of the total ropivacaine dose 40 hours after surgery (mean (standard deviation): 155.38 (4.55) versus 159.73 (7.87) mL, P = 0.016 ). Compared to the CEI group, the PIEB group had significantly lower numerical rating scale scores 3 hours (median [lower–upper quartiles]: 0[0–0.5] versus 3[0–5.5], P = 0.002 ), 24 hours (1[0–2] versus 3[1–4], P = 0.003 ), and 48 hours (1[0–2] versus 2[2–3.5], P = 0.002 ) after surgery. Conclusion . PIEB was better than CEI in terms of providing postoperative analgesia after open gynecological surgery under combined general-epidural anesthesia.